2019
DOI: 10.1111/odi.13226
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacotherapy in relieving the symptoms of burning mouth syndrome: A 1‐year follow‐up study

Abstract: ObjectiveBurning mouth syndrome (BMS) is a chronic intraoral burning sensation with no identifiable causes. In this study, we aim to demonstrate the effectiveness of treatment strategy using ethyl loflazepate monotherapy or in combination with milnacipran or amitriptyline.MethodA hospital‐based, retrospective study was conducted in 86 patients. The patients were divided into remission group and non‐remission group. The remission group comprised patients who were satisfied with their pain relief within a year o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 17 publications
0
7
0
1
Order By: Relevance
“…Moreover, unlike other benzodiazepine drugs and polaprezinc [16,17,18,19], EL has been known to act rapidly and last for quite a long time (i.e., half-life of 122 h), prevents or treats anxiety, and appears to have minimal side effects (e.g., less memory loss and drowsiness) [14,15]. Furthermore, El is safe for older individuals and has been well documented for treating anxiety and dental psychosomatic disorders [1][2][3]. Thus, we believed that EL would be an ideal therapy for the cases presented to our hospital.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, unlike other benzodiazepine drugs and polaprezinc [16,17,18,19], EL has been known to act rapidly and last for quite a long time (i.e., half-life of 122 h), prevents or treats anxiety, and appears to have minimal side effects (e.g., less memory loss and drowsiness) [14,15]. Furthermore, El is safe for older individuals and has been well documented for treating anxiety and dental psychosomatic disorders [1][2][3]. Thus, we believed that EL would be an ideal therapy for the cases presented to our hospital.…”
Section: Discussionmentioning
confidence: 99%
“…Ethyl lo azepate (EL) is a benzodiazepine derivative that is safe for elderly individuals and is well documented to treat anxiety and dental psychosomatic disorders [1][2][3]. Note worthily within the last two decades, research has also reported that this drug activates the gustatory cortex [4].…”
Section: Introductionmentioning
confidence: 99%
“…W piśmiennictwie dla wtórnego BMS stosuje się określenie "choroba pieczenia jamy ustnej" (ang. burning mouth disorder, BMD) [3,4]. Postawienie prawidłowej diagnozy następuje z opóźnieniem wynoszącym średnio od 34 do 41 miesięcy [5].…”
Section: Wprowadzenieunclassified
“…Ethyl loflazepate (EL) is a benzodiazepine derivative that is safe for elderly individuals and is well documented to treat anxiety and dental psychosomatic disorders [1][2][3]. Note worthily within the last two decades, research has also reported that this drug activates the gustatory cortex [4].…”
Section: Introductionmentioning
confidence: 99%